ELECTRICAL PROPERTIES OF THERMALLY EVAPORATED INDIUM TELLURIDE THIN FILMS (Biological Sciences - PJSIR, 2002)
Indium telluride thin films are prepared by thermal evaporation technique onto glass substrate held at room temperature at deposition pressure 2xl 0-4 Pa. Electrical studies of the films annealed in air at 400 K shows semiconducting behaviour. Thickness dependent  electrical  conductivity , activation  energy, aging  effect are also being  investigated. Activation  energyis found to decrease with film thickness. Thickness  dependent  conductivity  is  found  to  follow  Fuchs-Sondheimer  size effect theory. The Hall and thermoelectric measurements show that the films are p-type semiconductor having high carrier concentration  ofthe  order 1018/cm3.